Controlled release of drug molecules by pillararene-modified nanosystems. Issue 20 (23rd February 2022) - Yang, Qinglin; Xu, Weiwei; Cheng, Ming; Zhang, Siyun; Kovaleva, Elena G.; Liang, Feng; Tian, Demei; Liu, Jun-an; Abdelhameed, Reda M.; Cheng, Jing; Li, Haibing
Abstract : In this review, we summarize the advance of stimuli-responsive pillararene modified nanosystems for controlled release of drugs from the perspectives of decomposition release and gated release, and describe in detail the controlled release of recently developed photo-, pH-, thermal-, chemical- and multi-responsive nanosystems. Abstract : Stimuli-responsive nanosystems have attracted the interest of researchers due to their intelligent function of controlled release regulated by a variety of external stimuli and have been applied in biomedical fields. Pillar[ n ]arenes with the advantages of a rigid structure, electron holes and easy functionalization are considered as excellent candidates for the construction of host–guest nanosystems. In recent years, many pillararene modified nanosystems have been reported in response to different stimuli. In this feature article, we summarize the advance of stimuli-responsive pillararene modified nanosystems for controlled release of drugs from the perspectives of decomposition release and gated release, focusing on the control principles of these nanosystems. We expect that this review can enlighten and guide investigators in the field of stimuli-responsive controlled release.